2014
DOI: 10.1152/ajplung.00143.2013
|View full text |Cite
|
Sign up to set email alerts
|

Grainyhead-like 2 (GRHL2) distribution reveals novel pathophysiological differences between human idiopathic pulmonary fibrosis and mouse models of pulmonary fibrosis

Abstract: Chronic injury of alveolar lung epithelium leads to epithelial disintegrity in idiopathic pulmonary fibrosis (IPF). We had reported earlier that Grhl2, a transcriptional factor, maintains alveolar epithelial cell integrity by directly regulating components of adherens and tight junctions and thus hypothesized an important role of GRHL2 in pathogenesis of IPF. Comparison of GRHL2 distribution at different stages of human lung development showed its abundance in developing lung epithelium and in adult lung epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 45 publications
2
17
0
Order By: Relevance
“…However, the presence of these cells co‐expressing epithelial and mesenchymal markers denotes an incomplete transition, and not necessarily a complete transition of an epithelial cell into a ECM‐producing myofibroblast. Similar to these reports of incomplete transition, cells in alveolar epithelium of IPF lungs co‐expressed epithelial marker GRHL2 with EMT markers VIM or ZEB1 (Varma et al, ), indicating a hybrid E/M phenotype. Similarly, bronchiolar basal metaplastic cells in IPF patients lose E‐cadherin expression only partially (Morbini et al, ).…”
Section: Emt In Chronic Lung Diseasesupporting
confidence: 69%
“…However, the presence of these cells co‐expressing epithelial and mesenchymal markers denotes an incomplete transition, and not necessarily a complete transition of an epithelial cell into a ECM‐producing myofibroblast. Similar to these reports of incomplete transition, cells in alveolar epithelium of IPF lungs co‐expressed epithelial marker GRHL2 with EMT markers VIM or ZEB1 (Varma et al, ), indicating a hybrid E/M phenotype. Similarly, bronchiolar basal metaplastic cells in IPF patients lose E‐cadherin expression only partially (Morbini et al, ).…”
Section: Emt In Chronic Lung Diseasesupporting
confidence: 69%
“…4,[8][9][10][11]18,27,28 With regard to the clinical phenotype in our affected individuals, aside from the changes affecting the skin and oral mucosa, the other main features comprised deafness and asthma, although this was variably present. Three subjects (ED-01 IV-4 and IV-5 and ED-02 VI-3) had deafness that developed in early infancy (c.f.…”
mentioning
confidence: 89%
“…3,4 Biologically, GRHL2 contributes to formation of the epithelial barrier and wound healing, as well as neural-tube closure, maintenance of the mucociliary airway epithelium, and tumor suppression. [5][6][7][8][9][10][11] GRHL2 (MIM 608576) has been shown to regulate TERT (MIM 187270) expression and to enhance proliferation of epidermal keratinocytes; it also impairs keratinocyte differentiation through transcription inhibition of genes clustered at the epidermal differentiation complex 12 and regulates epithelial morphogenesis by establishing functional tight junctions. 13 GRHL2 is also present in the cochlear duct, 14 and mutations in human GRHL2 have been found in progressive autosomal-dominant hearing loss (DFNA28 [MIM 608641]), 15,16 and other polymorphic sequence variants in GRHL2 have been implicated in age-related hearing impairment and noise-induced hearing loss.…”
mentioning
confidence: 99%
“…Additionally, Grhl mutant mice are extensively used to model epithelial disease, ranging from hearing loss to cancer (Gordon et al, 2014). Studies of Grhl2 downstream genes in mice and in human bronchial cells revealed its key role in epithelial morphogenesis, cell adhesion, and motility (Gao et al, 2013;Varma et al, 2014;Aue et al, 2015;Gao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%